WiFi4EU: Techno-economic analysis of a key European Commission initiative for public connectivity - Julio Navío-Marco; Adrian Arévalo-Aguirre; Raquel Pérez-Leal (International Telecommunications Society (ITS), 2018)
This paper analyses the WiFi4EU initiative, the measures proposed by the European Commission (EC) to speed up public access to Wi-Fi throughout Europe in the coming years, ranging from rapid mechanisms to subsidising the infrastructure. We set out to analyse how these measures are incorporated into the EU policies for building a Digital Single Market and the EC's regulatory tradition, and what the impact of this initiative is likely to be. As this innovative initiative will have an effect upon the network deployments strategies of operators and countries and it has been drawn up in a climate of uncertainties and delays, the article puts all of this into the context of the current European regulation debate and conducts a techno-economic analysis to assess the expected impact of the initiative. We have observed a slight shift towards developmental models in the EC regulatory framework. Furthermore, the techno-economic analysis has revealed the limited extent of Community aid and the considerable variability of the equipment deployed and the expenditure involved. We have also highlighted the questionable formulation of the allocation mechanisms, and we have included certain examples or suggestions for optimisation.
Keywords: 330; WiFi4EU; network deployment; EC regulation; DSM; municipality